Determinants of the Physical Demand for Gold : Evidence from Panel Data - Starr, Martha (2012)
Although the role of gold in the world economy has declined since the gold standard was abandoned, it remains important as a central bank reserve, a hedge against risks, a barometer of geopolitical uncertainty, and an input for jewellery. While portfolio demand for gold has been well studied, determinants of physical demand are less understood. Certain emerging-market countries such as China and India import substantial amounts of gold, with several factors that may contribute: low financial development, need for precautionary savings and/or strong cultural valuation of gold itself. This article uses panel data on gold imports of 21 countries to examine determinants of physical demand. We find that determinants of physical demand differ from those of portfolio demand, and that they differ between the developed and developing worlds.